IDENTIFIKASI POPULASI GASTROPODA AIR TAWAR DI WADUK SAGULING DAN SEKITARNYA - Wahyono, Sri (Jurnal Teknologi Lingkungan, 2005)
This research has been carried out in Saguling, Jawa Barat. The aims of theresearch were to study the population of fresh water gastrophod and itsecological aspects. The research was done at three habitats which were thedam, paddy fields and ponds in three location : South Inlet, East Inlet and West Outlet of Saguling dam. It has been found 6 species of gastrophod which were Pomacea caniculata, Bellamya javanica, Lymnaea rubiginosa,Indoplanorbis exustus, Gyraulus convexiuscslus and Melanoides tuberculata. In all the habitats the density of species of Pomacea caniculata,Bellamya javanica and Lymnaea rubiginosa were relatively higher than others. While the highest dominantion index of gastrophod were at habitat of paddy fields in all locations and at habitat of ponds in East Inlet and West Outlet locations. Pomacea caniculata, Bellamya javanica and Lymnaea rubiginosa were dominant at habitat of pady fields and ponds. Furthermore, the highest gastrophod diversity index was at habitat of dam in South Inlet and West Outlet locations. All the gastrophod species were found in a group. On the other hand, there was a tendention that each habitat had a different gastrophod species.